2010
DOI: 10.1007/s12011-010-8836-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Expression Pattern of ZnTs, LC3, and Beclin-1 in Rat Hippocampus and Its Regulation by 3-Methyladenine Following Recurrent Neonatal Seizures

Abstract: It has been reported that autophagy and zinc transporters (ZnTs) both play the key roles in excitotoxicity, which is associated with cognitive deficits following developmental seizures. However, the influence of autophagy on acute phase ZnTs expression has never been studied. The present study sought to investigate the contribution of an autophagy inhibitor (3-methyladenine, 3-MA) on the regulation of ZnTs, microtubule-associated protein 1A/1B light chain 3 (LC3), and beclin-1 expression in rat hippocampus fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…LC3, a mammalian homologue of yeast Apg8p, has been regarded as a cellular marker for the formation of autophagosomes in mammalian cells which has been found localized in autophagosome membranes (Kabeya et al, ). In the line with our study, a previous study found that both of LC3 and Beclin‐1mRNA and protein expression were evidently increased after seizures, indicating the autophagy activation by recurrent neonatal seizures, which might be associated with the acute phase excitotoxicity (Ni, Feng, Gong, Tao, & Wu, ).…”
Section: Discussionsupporting
confidence: 92%
“…LC3, a mammalian homologue of yeast Apg8p, has been regarded as a cellular marker for the formation of autophagosomes in mammalian cells which has been found localized in autophagosome membranes (Kabeya et al, ). In the line with our study, a previous study found that both of LC3 and Beclin‐1mRNA and protein expression were evidently increased after seizures, indicating the autophagy activation by recurrent neonatal seizures, which might be associated with the acute phase excitotoxicity (Ni, Feng, Gong, Tao, & Wu, ).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our previously reported findings in acute toxicity studies with flurothyl-induced recurrent neonatal seizures which revealed up-regulated expressions of ZnT-1, ZnT-2, LC3 and beclin-1 of RS group. Pre-treatment with 3-MA remarkably attenuated seizure-induced ZnT-1, ZnT-2, LC3 and beclin-1 increase [5]. Additionally, linear correlations Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Statistical comparisons were carried out by nonparametric Kruskal-Wallis test. **P \ 0.01 versus control and CBI groups; *P \ 0.05 versus control and CBI groups; D P \ 0.05 versus control could be observed between LC3-Beclin1, LC3-ZnT-2, Beclin1-ZnT2, Beclin1-ZnT3 and among ZnT1-ZnT3 in control group, while the linear correlations could be observed between LC3-Beclin1, Beclin1-ZnT2 and Beclin1-ZnT3 in RS group [5]. These data, combined with our present findings that anti-apoptotic protein bcl-2 downregulated, strongly suggest that autophagic/apoptotic pathways may have been impacted at the protein level at the acute phase time point, which might be associated with the acute phase excitotoxicity and the long-term cognitive deficit.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations